(untitled) (Sunsari Technical College Journal, 2016)
Quark was prepared from cow milk by the optimization of different parameters like concentration of rennet, sugar percentage and flavor types. The rennet concentration used for optimization was 0.00139 %, 0.00234 %, 0.00278 % and 0.00468 %. In terms of acidity, texture, flavor and appearance. 0.00234 percent rennet was found significantly best product. The concentration of sugar in quark was varied in different proportion viz. 2, 4 and 5 %, among these 4 % was ranked best with respect to sensory properties. Flavor optimization with vanilla 125ppm without color addition was preferred significantly. Though the high quality life (HQL) of the optimized product was 45 days in deep frozen condition (-20°C), 6 days in refrigerated condition (-4°C). Yet, the product remained acceptable up to 2 days at room temperature (33 ± 2°C) and up to 15 days in refrigerated condition. Sunsari Technical College Journal 2015, 2(1):38-43